Tending the 'monthly flower:' a qualitative study of menstrual beliefs in Tigray, Ethiopia - L. Lewis Wall; Kibrom Teklay; Alem Desta; Shewaye Belay (BMC, 2018)
Abstract Background Menstruation is a universal aspect of human female reproductive life. Management of menstrual flow presents hygiene challenges to girls and women in low-income countries, especially when they first start their periods. As part of a project to improve menstrual hygiene management in the Tigray Region of Ethiopia, we explored the local understanding of menstruation through focus-group discussions and individual interviews. Methods A detailed ethnographic survey of menstrual beliefs was carried out through 40 focus group discussions, 64 in-depth key informant interviews, and 16 individual case histories in the Tigray Region of northern Ethiopia. A total of 240 individuals participated in six types of focus groups (pre-menarchal girls, menstruating adolescents, married women of reproductive age, post-menopausal women, adolescent males, and married men). In-depth interviews were also carried out with 80 individuals, including Orthodox Christian priests, imams from the Muslim community, principals of primary and secondary schools, teachers and nurses, as well as menstruating schoolgirls and women. Audio data were transcribed and translated, then broken down into discrete codes using Atlas Ti software (version 7.5.4, Atlas.ti Scientific Software Development Mnbh, Berlin) and further grouped into related families and sub-families based on their content. The results were then synthesized to produce a cohesive narrative concerning menstruation in Tigray. Results Recurrent themes identified by participants included descriptions of the biology of menstruation (which were sometimes fanciful); the general unpreparedness of girls for menarche; cultural restrictions imposed by menstruation on females (particularly the stigma of ritual uncleanliness in both Christian and Muslim religious traditions); the prevalence and challenges of unmet menstrual hygiene needs at schools (including lack of access to sanitary pads and the absence of acceptable toilet/washing facilities); and the stigma and shame associated with menstrual hygiene accidents in public. Conclusions Changes in the educational system in northern Ethiopia are required to improve student understanding of the biology of menstruation, to foster gender equity, to overcome the barriers to school attendance presented by poor menstrual hygiene management, and to create a society that is more understanding and more accepting of menstruation.